Financial markets and instruments in private international law / Augustin Gridel ; preface by Louis D'Avout ; foreword by Christine Lagarde. - Gridel, Augustin (European Union law series., 2025)
In banking and finance, transnationality permeates the day-to-day professional life and makes the dedicated lawyer an internationalist by necessity. There are good reasons for this: the intangible nature of services, the desire of operators even regulated to conquer foreign markets; sometimes because of the extraterritorial spread of local policies relating to the person of the operators or the products marketed. Although it does not always have a good reputation, private international law, with its promise of a widely understood conflict of law discipline, is making inroads into the legal practice of this specialised and globalised sector.